CRISPR/Cas Genome Editing in Engineering Plant Secondary Metabolites of Therapeutic Benefits - Das, T.; Ghorai, M.; Pandey, D.K.; Radha; Thakur, M.; Rathour, S.; Al-Tawaha, A.R. (Springer Nature, 2022)
Plants hold the ability to produce wide types of bioactive secondary metabolites. Having emerged in the pregenomic era, increasingly more biosynthetic genes are being discovered in plants, leading to the discovery of new types of bioactive secondary metabolites. Utilisation of classical techniques is limited that hampers the discovery of pharmacologically important secondary metabolites. However, the development of CRISPR (clustered regularly interspaced short palindromic repeats)/Cas (CRISPR associated protein)-based tools may alleviate this impasse. This chapter briefly presents existing information about the CRISPR/Cas9 system, and by what implies it was engineered to enhance important secondary metabolite production in plants. CRISPR/Cas systems have been among the most versatile genome editing tools available, revolutionising molecular biology. This chapter intends to highlight and discuss the lasting challenges of CRISPR/Cas-based genome editing and the improvement of secondary metabolite amount in plant natural product engineering. The plants canvassed in this chapter include Atropa belladonna, Brassica napus, Camelina sativa, Dendrobium officinale, Dioscorea zingiberensis, Glycine max, Humulus lupulus, Papaver somniferum and Salvia miltiorrhiza. Additionally, we highlight the prospects of using CRISPR/Cas in plant secondary metabolite engineering. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.
Keywords: Crispr/Cas9; Medicinal Plants Genome Editing; Metabolites; Plant Natural Products